Hubungan riwayat overweight dan durasi tidur dengan berat badan - Sahita, Cici; mukti, Akbar rizza; tiara, deva nattassya; harwati, hadisna putri (Indonesian Journal of Nutrition Science and Food; Vol 2 No 2 (2023): Januari 2023, 2023)
Overweight is a health problem that occurs in young people and adults. Obesity (fat) can be influenced by many factors such as age, genetics, gender, diet, physical activity, lifestyle and sleep duration. This research was conducted to find out whether there is a relationship between previous overweight and sleep duration with body weight. The method used is a food recall questionnaire 3 times 24 hours and a sleep quality questionnaire with the Cross Sectional method. The population of this study were all Ivet Semarang university students with conditions over 18 years of age. The sample size is 30 students and the samples are taken randomly. The dependent variable is overweight and sleep duration and the independent variable is body weight. Data is tested using Chi-Square. The results of this study showed that there was no relationship between history of overweight and sleep duration with a P-value of more than 0.05, which means that there was no relationship between the independent variable and the dependent variable in this study. It is hoped that this research can become literacy for future researchers and increase respondents' knowledge about obesity and sleep duration as well as increase literacy for campuses to improve learning methods to be more effective, creative and efficient so that the quality of student knowledge can increase.